Trends in the methodology of media consumption study in the field of cinema in Russia - Igorevna Nikitina, Tatyana (2021)
The relevance of the topic is conditioned by the need for scientific understanding of media analytics and a qualitative understanding of its methods as promotion tools, as well as for the introduction of the research stage of media consumption into the film production process to popularize and further promote domestic film products among the Russian audience. In the Russian film industry, this experience is especially necessary within modern economic conditions. The need to ensure the financial success of Russian film products, which are subsidized by the state, has led to the interest in finding new approaches promoting and increasing the loyalty of the cinema audience, which is especially important at a time when only 1 out of 10 domestic films pays for their film production during the distribution period.